Coronavirus disease 2019 (COVID-19) research agenda for healthcare epidemiology. (25th February 2022) - Mody, Lona; Akinboyo, Ibukunoluwa C.; Babcock, Hilary M.; Bischoff, Werner E.; Cheng, Vincent Chi-Chung; Chiotos, Kathleen; Claeys, Kimberly C.; Coffey, K. C.; Diekema, Daniel J.; Donskey, Curtis J.; Ellingson, Katherine D.; Gilmartin, Heather M.; et al.
Abstract: This SHEA white paper identifies knowledge gaps and challenges in healthcare epidemiology research related to coronavirus disease 2019 (COVID-19) with a focus on core principles of healthcare epidemiology. These gaps, revealed during the worst phases of the COVID-19 pandemic, are described in 10 sections: epidemiology, outbreak investigation, surveillance, isolation precaution practices, personal protective equipment (PPE), environmental contamination and disinfection, drug and supply shortages, antimicrobial stewardship, healthcare personnel (HCP) occupational safety, and return to work policies. Each section highlights three critical healthcare epidemiology research questions with detailed description provided in supplementary materials. This research agenda calls for translational studies from laboratory-based basic science research to well-designed, large-scale studies and health outcomes research. Research gaps and challenges related to nursing homes and social disparities are included. Collaborations across various disciplines, expertise and across diverse geographic locations will be critical.